Angiotensin-converting enzyme inhibitor captopril ameliorates renal damage in a rat model of thermal injury - ALTURFAN, EBRU IŞIK; ŞENER, GÖKSEL (WALTER DE GRUYTER GMBH, 2013)
Background: Burn is a posttraumatic inflammatory condition accompanied by both local and distant effects leading to intense inflammation, tissue damage, and infection. Acute renal failure is a well-known complication of severe burns and is an important factor leading to an increase in mortality. Objective: To determine the effect of captopril treatment on renal damage in a rat model of thermal injury by evaluating oxidant antioxidant system parameters, sialic acid levels, glutathione-S-transferase (GST), and tissue factor (TF) activities. Methods: Under ether anesthesia, the shaved dorsum of the rats was exposed to a 90 degrees C water bath for 10 seconds to induce burn injury. Captopril (1 mg/kg) or saline was administered intraperitoneally immediately after, and at 24 hours after burn injury. Rats were decapitated at 48 hours following the burn injury and trunk blood was collected to assay blood urea nitrogen (BUN) and creatinine concentrations. To evaluate the presence of oxidant injury, kidney tissue samples were taken to determine malondialdehyde (MDA), glutathione (GSH), sialic acid levels, and the activities of superoxide dismutase (SOD), catalase, GST, and TF. In the sham group the same protocol was applied except that the dorstun was dipped in a 25 degrees C water bath for 10 seconds. Results: Severe skin scald injury (30% of total body surface area) caused significant decreases in GSH level, SOD and catalase activities, and significant increases in TF and GST activities, and sialic acid levels. Treatment of rats with captopril (1mg/kg) significantly elevated the reduced GSH levels, SOD and catalase activities, while it decreased MDA, sialic acid levels, GST and TF activities. Conclusions: The present study showed for the first time that, captopril scavenging of reactive free radicals, normalizing the activities of TF and GST seems to be a promising agent for restoring renal damage following thermal trauma.
Keywords: Burn; kidney; captopril; catalase; glutathione; lipid peroxidation; sialic acid; superoxide dismutase; tissue factor; TISSUE LIPID-PEROXIDATION; SUPEROXIDE-DISMUTASE; OXIDATIVE STRESS; N-ACETYLCYSTEINE; BURN INJURY; PLASMA; BLOOD; GLUTATHIONE; PATHWAY; MOUSE